Keeping patent airways - Ige Afuso, Manuel (2010)
Maintaining patent airways is an important task in the care of critically ill patients inside or outside the hospital, so the initial assessment is crucial (using the WLF approach [watch, listen and feel]), and there is where we will determine the airways patency, as well as patients with a poor respiratory pattern or those requiring assisted ventilation. In order to have a patent airway we may perform the heat tilt-chin lift, which should not be performed if a cervical lesion is suspected; in these patients, the jaw thrust maneuver may be performed. Other measures are the placement of an oro-pharyngeal or naso-pharyngeal cannula, so that airway obstruction caused by soft tissue from the mouths floor (tongue) may be alleviated. Manual ventilation may be performed using a bag-valve-mask device, and it is more efficient if two operators are available, also, the laryngeal mask or combitube may be used, being these devices easy to place, without the need of further knowledge in CPR. Oro-tracheal intubation is still the most effective measure for preserving patency of the airways, but its use requires experienced personnel, particularly when intubation may become more difficult.